2018
DOI: 10.1159/000488411
|View full text |Cite|
|
Sign up to set email alerts
|

MicroRNA-30a Suppresses the Activation of Hepatic Stellate Cells by Inhibiting Epithelial-to-Mesenchymal Transition

Abstract: Background/Aims: The activation of hepatic stellate cells (HSCs) is considered as a pivotal event in liver fibrosis and epithelial-mesenchymal transition (EMT) process has been reported to be involved in HSC activation. It is known that microRNAs (miRNAs) play a pro-fibrotic or anti-fibrotic role in HSC activation. Recently, emerging studies show that miR-30a is down-regulated in human cancers and over-expression of miR-30a inhibits tumor growth and invasion via suppressing EMT process. However, whether miR-30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Overexpression of miR-30a inhibits EMT via downregulation of snail family transcriptional repressor 1 (Snai1), leading to suppress HSCs activation in liver fibrosis. 34 In our current study, we identified that miR-875-5p was markedly decreased in human cirrhotic tissues, fibrotic liver tissues, and primary HSCs from CCL 4 mice, suggesting low levels of miR-875-5p are beneficial for liver fibrosis progression. Interestingly, we demonstrated that icariin could enhance miR-875-5p expression, and knockdown of miR-875-5p impaired the effect of icariin on murine HSCs.…”
Section: Then How Does Icariin Inhibited Emt Of Hscs?mentioning
confidence: 51%
See 1 more Smart Citation
“…Overexpression of miR-30a inhibits EMT via downregulation of snail family transcriptional repressor 1 (Snai1), leading to suppress HSCs activation in liver fibrosis. 34 In our current study, we identified that miR-875-5p was markedly decreased in human cirrhotic tissues, fibrotic liver tissues, and primary HSCs from CCL 4 mice, suggesting low levels of miR-875-5p are beneficial for liver fibrosis progression. Interestingly, we demonstrated that icariin could enhance miR-875-5p expression, and knockdown of miR-875-5p impaired the effect of icariin on murine HSCs.…”
Section: Then How Does Icariin Inhibited Emt Of Hscs?mentioning
confidence: 51%
“…For example, Zhang et al, reported that miR‐30a was downregulated in human cirrhotic tissues and fibrotic liver tissues from CCL 4 rats. Overexpression of miR‐30a inhibits EMT via downregulation of snail family transcriptional repressor 1 (Snai1), leading to suppress HSCs activation in liver fibrosis . In our current study, we identified that miR‐875‐5p was markedly decreased in human cirrhotic tissues, fibrotic liver tissues, and primary HSCs from CCL 4 mice, suggesting low levels of miR‐875‐5p are beneficial for liver fibrosis progression.…”
Section: Discussionmentioning
confidence: 65%
“…Activation of hepatic stellate cells (HSCs) involves the transition from a quiescent to a proliferative, migratory and fibrogenic phenotype (i.e., myofibroblast) which is characteristic of liver fibrogenesis. To date, multiple cell-surface, cytoplasmic and nuclear molecular signals and pathways have been reported to modulate HSC activation, including cytokines ( Syn et al, 2011 , 2012 ); adipocytokines ( Saxena and Anania, 2015 ; Coombes et al, 2016 ); Toll-like receptors (TLRs) ( Chou et al, 2012 ; Seo et al, 2016 ); Interleukins (ILs) ( Jiao et al, 2016 ); collagen receptors ( Liu et al, 2017 ); nuclear receptors ( Beaven et al, 2011 ; Ding et al, 2013 ; Li et al, 2014 ; Palumbo-Zerr et al, 2015 ; Duran et al, 2016 ); G protein-coupled receptors (GPCRs) ( Li et al, 2015 , 2016a ; Le et al, 2018 ); autophagy ( Thoen et al, 2011 , 2012 ; Hernández-Gea and Friedman, 2012 ; Hernández-Gea et al, 2012 ); endoplasmic reticulum stress ( Hernández-Gea et al, 2013 ; Koo et al, 2016 ); oxidative stress ( Lan et al, 2015 ; Ou et al, 2018 ); epigenetics ( Coll et al, 2015 ; Hyun et al, 2016 ; Kweon et al, 2016 ; Huang et al, 2018 ; Zheng et al, 2018 ); cell metabolism ( Nwosu et al, 2016 ; Du et al, 2018 ; Franko et al, 2018 ; Zhang et al, 2018 ), etc. In addition, extracellular/paracrine signals from resident and inflammatory cells including hepatocytes ( Zhan et al, 2006 ), macrophages ( Pradere et al, 2013 ), natural killer cells ( Glässner et al, 2012 ), natural killer T cells ( Wehr et al, 2013 ), liver sinusoidal endothelial cells (LSECs) ( Xie et al, 2012 ), platelets ( Kurokawa et al, 2016 ), and B cells ( Thapa et al, 2015 ) further promote HSC activation.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of HSCs is considered an important event in liver fibrosis, and epithelial–mesenchymal transition (EMT) plays an important role in HSC activation [ 9 ]. HSCs have several important functions under both physiological and pathological conditions associated with sinusoids [ 10 ].…”
Section: Discussionmentioning
confidence: 99%